A new cavefish species from Southwest China, Sinocyclocheilus gracilicaudatus sp. nov. (Teleostei: Cypriniformes: Cyprinidae) - Wang, Dan; Zhao, Yahui; Yang, Junxing; Zhang, Chunguang (Zootaxa, 2014)
One new species is added to the genus Sinocyclocheilus, the largest cyprinid genus in China and the largest cavefish genus in the world. Sinocyclocheilus gracilicaudatus sp. nov. is similar to S. donglanensis but differs to other congeners in having normal eyes and scaled body, curved lateral line with 59–64 lateral-line scale rows, half-hard dorsal fin spine, 8 gill rakers and 8 predorsal vertebrae. Compared to S. donglanensis, the new species has a longer and more narrow caudal peduncle (caudal peduncle length 21.3-22.7% vs. 16.8–20.4% of SL; caudal peduncle depth 10.5–12.0% vs. 12.5–15.5% of SL), smaller eyes (eye diameter 5.8–8.3% vs. 6.5–10.9% of SL) and longer barbels (maxillary barbel length 16.6–24.3% vs. 11.1–21.1 % of SL; rictal barbel length 19.5–21.6% vs. 11.3–21.1% of SL). The new species is distributed in a subterranean river, belonging to the Longjiang River system; S. donglanensis occurs in the Hongshuihe River system, a system separate from that where the former species occurs.